Development of Interactive Media Scratch-Based Educational Games on Environmental Conservation Materials in Elementary Schools - Putri Sofiatul Maola; Dede Margo Irianto (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to develop interactive media Scratch-based educational games on grade V environmental conservation material in elementary schools and measure the feasibility of the media. This research used the D&D (Design and Development) method with the ADDIE model research design, which consists of 5 stages (Analysis, Design, Development, Implementation, and Evaluation). Data feasibility collection was done through the validation of material experts and media experts, as well as response questionnaires given to teachers and students. The data analysis technique used descriptive analysis techniques, which include qualitative and quantitative data. The results of the feasibility test from the material validator got a percentage score of 91.67%, which belongs to very feasible category; the media validator got a result of 92.5%, which belongs to very feasible category. The teacher response questionnaire obtained a result of 97.5%, with a very feasible category, and the student response questionnaire obtained a result of 95.75%, which belongs to very feasible category. Based on the resulting research, the interactive media developed, namely Scratch media, was very feasible to be used as a digital technology-based learning media innovation in elementary schools.